2008
DOI: 10.3233/jad-2008-14202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Saturated Fat and High Cholesterol Diet on Memory and Hippocampal Morphology in the Middle-Aged Rat

Abstract: Diets rich in cholesterol and/or saturated fats have been shown to be detrimental to cognitive performance. Therefore, we fed a cholesterol (2%) and saturated fat (hydrogenated coconut oil, Sat Fat 10%) diet to 16-month old rats for 8 weeks to explore the effects on the working memory performance of middle-aged rats. Lipid profiles revealed elevated plasma triglycerides, total cholesterol, HDL, and LDL for the Sat-Fat group as compared to an iso-caloric control diet (12% soybean oil). Weight gain and food cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
205
2
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(228 citation statements)
references
References 72 publications
17
205
2
4
Order By: Relevance
“…33,34 In particular, it was reported that rats fed with a high-fat diet (soybean oil and cholesterol supplemented, no fructose) for 8 weeks present a diminished staining of MAP-2 in the hippocampus, and that this reduction is correlated with memory errors. 16 Microtubule-associated protein 2 modifies and controls microtubule assembly and spacing within dendrites. Thus, a fine regulation of MAP-2 dynamics can alter hippocampal plasticity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 In particular, it was reported that rats fed with a high-fat diet (soybean oil and cholesterol supplemented, no fructose) for 8 weeks present a diminished staining of MAP-2 in the hippocampus, and that this reduction is correlated with memory errors. 16 Microtubule-associated protein 2 modifies and controls microtubule assembly and spacing within dendrites. Thus, a fine regulation of MAP-2 dynamics can alter hippocampal plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Studies performed in animal models of diet-induced obesity and InsRes such as longterm HFFD feeding show a deficient execution in memory and learning tasks. [11][12][13][14][15][16] These cognitive alterations were associated with functional and structural changes in the hippocampus, such as reduced number and complexity of dendritic spines in the CA1 subfield, altered establishment of long-term potentiation and long-term depression, and diminished dentate gyrus (DG) neurogenesis. [11][12][13] The latter was correlated with decreased expression of brain derived neurotrophic factor, cyclic AMP-response element-binding protein and the synaptic proteins synapsin, and stargazin.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers evaluate the effect of a diet high in cholesterol and fat (diet containing 2% cholesterol and 10% hydrogenated coconut oil). The results showed a failure in working memory, here evaluated with the water radial arm maze as well as elevated lipids profile and reduce expression of Map-2 as an indicator of alteration of dendritic integrity, which correlates with memory mistakes measured in the test, and increase in inflammation markers such as microglia activation [52]. In a study carried out with Sprague-Dawley rats, which were fed for 7 days with high fat and fructose, several hippocampal alterations, such as decreased insulin signaling, were reported.…”
Section: Impact On Brain Morphology Plasticity and Cognitionmentioning
confidence: 99%
“…Murray et al showed that only 9 days of a high-fat diet was sufficient to cause physical impairment on a treadmill and cognitive impairment in the water maze (121). When 16-month-old rats were fed diets high in fat and cholesterol they made more errors in a test of working memory especially when memory loads were high, and they also showed altered hippocampal morphology (60). Similar studies of mice showed that high-fat diets worsen performance in learning and memory tests (49,181).…”
Section: Animal Studiesmentioning
confidence: 99%